2020
DOI: 10.1038/s41598-020-61613-y
|View full text |Cite
|
Sign up to set email alerts
|

A universal opportunity model for human mobility

Abstract: Predicting human mobility between locations has practical applications in transportation science, spatial economics, sociology and many other fields. For more than 100 years, many human mobility prediction models have been proposed, among which the gravity model analogous to Newton's law of gravitation is widely used. Another classical model is the intervening opportunity (IO) model, which indicates that an individual selecting a destination is related to both the destination's opportunities and the intervenin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 69 publications
(115 reference statements)
1
32
0
Order By: Relevance
“…Macroscopically, in the field of human migration, the so called gravity law has been widely applied [21][22][23] . Besides the gravity model, the intervening opportunity class model, where the flow amount is proportional to the opportunity of the destination and inversely proportional to the intervention opportunity between the origin and the destination, has been widely studied [24][25][26][27][28] . Also, probabilistic human mobility prediction are widely performed for congestion and advertisement optimization [29][30][31][32] .…”
Section: Detail Observation Of Human Locations Became Available Recenmentioning
confidence: 99%
“…Macroscopically, in the field of human migration, the so called gravity law has been widely applied [21][22][23] . Besides the gravity model, the intervening opportunity class model, where the flow amount is proportional to the opportunity of the destination and inversely proportional to the intervention opportunity between the origin and the destination, has been widely studied [24][25][26][27][28] . Also, probabilistic human mobility prediction are widely performed for congestion and advertisement optimization [29][30][31][32] .…”
Section: Detail Observation Of Human Locations Became Available Recenmentioning
confidence: 99%
“…4 a, c. In that case, the result indicated that the underlying mechanism of the decision-making process is not the same as the commuting flow. Migrants may tend to place high importance on the destination opportunity benefit rather than the distance to the destination as mentioned in a previous study 44 .…”
Section: Discussionmentioning
confidence: 72%
“…Although several parameter-free and universal models for human mobility are proposed 30 , 38 , 43 , 46 , we used the OPS model for comparison to the newly proposed model, because the model has the derivation and high predictability regardless of spatial scale such as inter-city and intra-city scales 43 , 44 .…”
Section: Methodsmentioning
confidence: 99%
“…The Sørensen-Dice coefficient is often used to compare models against real data 17 , 18 , 21 26 and is sometimes referred to as the ‘common part of commuters’ in this context. This is defined as for model values and flow data from site i to site j .…”
Section: Methodsmentioning
confidence: 99%
“…However, there are problems with the underlying statistical basis for many of the most popular approaches. The Sørensen-Dice coefficient is often used to compare models against real data 17,18,[21][22][23][24][25][26] and is sometimes referred to as the 'common part of commuters' in this context. This is defined as DSC = ij min( F ij , F ij )/ ij F ij for model values F ij and flow data F ij from site i to site j.…”
Section: Common Techniques For Comparing Modelsmentioning
confidence: 99%